2019
DOI: 10.1021/acs.jafc.9b03827
|View full text |Cite
|
Sign up to set email alerts
|

Alterations of the Brain Proteome and Gut Microbiota in d-Galactose-Induced Brain-Aging Mice with Krill Oil Supplementation

Abstract: Brain aging is commonly associated with neurodegenerative disorders, but the ameliorative effect of krill oil and the underlying mechanism remain unclear. In this study, the components of krill oil were measured, and the antiaging effects of krill oil were investigated in mice with d-galactose (d-gal)-induced brain aging via proteomics and gut microbiota analysis. Krill oil treatment decreased the expression of truncated dopamine- and cAMP-regulated phosphoproteins and proteins involved in the calcium signalin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 46 publications
1
8
0
Order By: Relevance
“…Hence, maintaining the normal oxidation-reduction balance of the organism is essential to the overall health of human beings. According to the reported antioxidant mechanism, living organisms remove excessive oxygen free radicals by scavenging ROS precursors, chelating with metal ions involved in the formation of ROS, and increasing endogenous antioxidant defenses in the body [ 4 ]. Given the important impact of oxidative stress on living organisms, adding various antioxidant supplements into the daily diet is essential to antagonize oxidative stress and maintain normal body organs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, maintaining the normal oxidation-reduction balance of the organism is essential to the overall health of human beings. According to the reported antioxidant mechanism, living organisms remove excessive oxygen free radicals by scavenging ROS precursors, chelating with metal ions involved in the formation of ROS, and increasing endogenous antioxidant defenses in the body [ 4 ]. Given the important impact of oxidative stress on living organisms, adding various antioxidant supplements into the daily diet is essential to antagonize oxidative stress and maintain normal body organs.…”
Section: Introductionmentioning
confidence: 99%
“…d -gal can be converted to galactitol after prolonged injection of high-dose. Because galactitol cannot be decomposed, and accumulates in the cells, leading to enhanced ROS eventually [ 4 , 9 , 10 ]. The present study evaluated the antioxidant capacity of PPF in vivo, investigated the underlying mechanism, and explored the correlation between the gut microbiota and antioxidant status in the d -gal-induced oxidative stress mouse model.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, diets were considered to play important roles in brain aging through the modulation of gene and protein expression [5]. Recent researchers suggested that dietinduced changes of gut microbiota also affected age-related pathogenesis [6]. Serine is a nutritionally nonessential amino acid, but it is a major substrate for the synthesis of glutathione.…”
Section: Introductionmentioning
confidence: 99%
“…According to an experimental model, mice fed for 12 weeks with a high fat and high sugar diet showed obesity and hyperlipidemia. Treatment with a high dose (600 µg/g/day) of krill oil, but not with lower doses (100 µg/g/day or 200 µg/g/day) improved the microbiotic alteration and cardiometabolic parameters [126].…”
Section: Krill and Inflammatory Bowel Diseases And Gut Microbiotamentioning
confidence: 91%